Cell wall integrity signaling and innate immunity in plants - Nuhse, Thomas S. (Frontiers in Plant Science, 2012)
All plant pathogens and parasites have had to develop strategies to overcome cell walls in order to access the host’s cytoplasm. As a mechanically strong, multi-layered composite exoskeleton, the cell wall not only enables plants to grow tall but also protects them from such attacks. Many plant pathogens employ an arsenal of cell wall degrading enzymes, and it has long been thought that the detection of breaches in wall integrity contributes to the induction of defence. Cell wall fragments are danger-associated molecular patterns or DAMPs that can trigger defence signalling pathways comparable to microbe-associated patterns (MAMPs), but the picture is likely to be more complicated. A wide range of defects in cell wall biosynthesis leads to enhanced pathogen resistance. We are beginning to understand the essential role of cell wall integrity surveillance for plant growth, and the connection of processes like cell expansion, plasma membrane-cell wall contact and secondary wall biosynthesis with plant immunity is emerging.